2019
DOI: 10.1007/s00508-018-1418-9
|View full text |Cite
|
Sign up to set email alerts
|

„Diabesity“ – Adipositas und Typ-2-Diabetes (Update 2019)

Abstract: Zusammenfassung Adipositas und Typ-2-Diabetes werden seit einigen Jahren vermehrt unter dem Namen "Diabesity" zusammengefasst. Das trägt dem Umstand Rechnung, dass die Adipositas dem Diabetes in den meisten Fällen häufig vorangeht und wohl der wichtigste Faktor in der weltweiten Zunahme des Typ-2-Diabetes ist. Der Body-Mass-Index (BMI) ist individuell betrachtet ein sehr grobes Maß der Körperverfettung. Sogar Normalgewichtige können bei Muskelmangel zu viel Körperfett aufweisen (Sarkope-H. Toplak ( ) Klinische

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 58 publications
1
21
0
7
Order By: Relevance
“…Indeed, based on data from meta-analyses (12,(22)(23)(24)(25)(26)(27)(28)(30)(31)(32) , our model was parameterised so that an increase in energy intake resulted in an increased T2D risk, as a function of the BMI and level of physical activity of the subjects. Under this model, a change in energy intake is an important factor for risk estimates, in line with the importance of energy imbalances in being overweight and of being overweight in the T2D risk, as highlighted in the literature (44) . However, although energy density and portion size are key drivers of a long-term energy imbalance, mechanisms for adjustment to subsequent energy intake should partly buffer the impact of a difference in energy content between two dishes on long-term energy intake.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, based on data from meta-analyses (12,(22)(23)(24)(25)(26)(27)(28)(30)(31)(32) , our model was parameterised so that an increase in energy intake resulted in an increased T2D risk, as a function of the BMI and level of physical activity of the subjects. Under this model, a change in energy intake is an important factor for risk estimates, in line with the importance of energy imbalances in being overweight and of being overweight in the T2D risk, as highlighted in the literature (44) . However, although energy density and portion size are key drivers of a long-term energy imbalance, mechanisms for adjustment to subsequent energy intake should partly buffer the impact of a difference in energy content between two dishes on long-term energy intake.…”
Section: Discussionsupporting
confidence: 55%
“…However, using body mass (or body mass index) as a measure of obesity is extremely crude [ [81] , [82] , [83] ] and may miss more subtle effects on body composition changes. That appears to be the case here, because although food intake increased enormously as it got colder this intake was insufficient to meet the elevated thermoregulatory requirements, and increasingly so as it got colder.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, this procedure is indicated when the BMI > 35 kg/m 2 (this value corresponds to a type II obesity) and it is necessary to be incorporated into a proper context of care and permanent medical assistance [ 64 ]. However, other studies demonstrated that this procedure may produce higher benefits in patients with a BMI ≥ 27 compared to intensive medical therapy in terms of glycaemia controlling and weight loss, reporting better results even in their quality of life [ 65 ], thus denoting the possibility of considering this alternative in the clinical management of diabesity. On the other hand, despite its effectivity, its high price, the possible complications associated, and the invasiveness of the procedure are other factors to be taken into account when selecting the proper therapy for each patient [ 66 ].…”
Section: Clinical Management Of Diabesitymentioning
confidence: 99%